Social Media Disorder, Mental Health, and Validation of the Chinese Version of 27-Item Social Media Disorder Scale in Chinese College Students - Hui Lei; Yaqing Huang; Ya Chai; Xiaocui Zhang; Xiaocui Zhang; Xiaocui Zhang (Frontiers Media S.A., 2022)
ObjectiveWith the widespread use of social media, excessive use of social media may lead to problematic behaviors such as social media disorder, which has a negative impact on teenagers' mental health. Thus, it is an urgent need to provide a measurement tool to assess social media addiction in different cultures. The aim of this study was to assess the psychometric properties of the Chinese version of 27-item Social Media Disorder (SMD) Scale (developed using the diagnostic criteria of DSM-V Internet Gaming Disorder) in college students, and to verify its impact on mental health.MethodsTwo online surveys were conducted among a total of 1,539 Chinese college students, including 1,316 subjects in sample 1 and 223 subjects in sample 2. The discrimination, criterion validity, construct validity and reliability of the Chinese version of SMD-27 scale were examined.ResultsThe Chinese version of SMD-27 scale showed excellent psychometric properties. The item-total correlation coefficients of the scale ranged from 0.31 to 0.56, and the item-dimension correlations of the scale ranged from 0.459 to 0.834. Findings from confirmatory factor analysis indicated a great fit of the model of the Chinese version of SMD-27, with CFI = 0.956, TLI = 0.951, RMSEA = 0.036 in sample one and CFI = 0.970, TLI = 0.967, RMSEA = 0.040 in sample two, thus confirming the second-order factor structure of the scale. The SMD-27 scale showed good internal consistency between two different samples with their respective Cronbach's alpha of 0.87 and 0.92, and good test-retest reliability over a period of 1 month. In addition, multiple regression results generally supported the impact of social media addiction on mental health.ConclusionThis study provides evidence that the Chinese version of SMD-27 scale is applicable to Chinese college populations, and it is a promising tool for the study of social media addiction in China.